The Role of BINWIN (Marriage Counseling) by KUA of Wampu Subdistrict in Protecting Wives from Husbands Addicted to Narcotics in Maintaining Household Harmony (A Case Study in Ampera Hamlet, Wampu Subdistrict - Avanti, Nabila Shakira; Iqbal, Muhammad Nur (LEGAL BRIEF, 2025)
This study aims to explore the impact of drug use by husbands on household harmony and the role of marriage guidance ( Binwin ) in Wampu District, especially in handling cases of households affected by drug addiction. The method used is a phenomenological approach with qualitative descriptive analysis, through in-depth interviews with wives of drug addicted husbands and KUA officers. The results of the study indicate that drug use by husbands causes physical, psychological, and economic damage in the household, which is reflected in relationship tensions, domestic violence (KDRT), and heavy financial burdens on wives. Wives often feel depressed, and children experience fear and emotional trauma. On the other hand, the role of Binwin carried out by KUA in overcoming this problem has proven to be limited because the material taught is still too general and does not cover actual issues such as drugs, domestic violence, and mental health in marriage. This study suggests the need for the development of more specific Binwin materials and cross-agency cooperation to provide more comprehensive solutions for families affected by drugs.